Effect of Particle Sizes on Thermal Conductivity of Five Wood Species from the Family of Sterculiaceae, Moraceae, and Ulmaceae - T. M. Aramide; O. F. Famutimi (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate effect of particle sizes on thermal conductivity of five wood species from the family of Sterculiaceae, Moraceae, and Ulmaceae using Differential Thermal Analyser after pulverizing and sieving wood materials into different maximum particle sizes of 106 μm, 300 μm, 425 μm, 850 μm and 1180 μm respectively with appropriate mesh. The result of the thermal conductivity ranged from 0.0100 to 0.0492 Wm-1 K-1. It was observed from the result that thermal conductivity of wood materials is dependent of particle sizes. This suggests that the performance of the material could be influenced by particle size. Builders are encouraged to work hand in hand with researchers so as to have a deep understanding of insulating material to be used in building constructions.